Navigating Pneumoperitoneum in Severe HFrEF: A Case Report on a Physiology-Based Anesthetic Strategy - Setia Hilmi Mustajabah; Andy Nugroho; Muhammad Ridho Aditya (HM Publisher, 2025)
Laparoscopic surgery in patients with severe heart failure with reduced ejection fraction (HFrEF) presents a formidable anesthetic challenge. The cardiovascular sequelae of pneumoperitoneum can precipitate acute hemodynamic collapse in a myocardium with minimal contractile reserve. This report details the anesthetic management of a high-risk patient with an extremely low ejection fraction undergoing laparoscopic cholecystectomy, focusing on a physiology-based approach. A 63-year-old, 72 kg male with severe HFrEF (ejection fraction 24%) and NYHA class III symptoms was scheduled for laparoscopic cholecystectomy. His ASA physical status was IV. Preoperative optimization ensured he was euvolemic and on guideline-directed medical therapy. Anesthetic induction was achieved with fentanyl (1.4 mcg/kg), atracurium (0.35 mg/kg), and ketamine (1 mg/kg). Following CO₂ insufflation, the patient developed profound bradycardia (42 bpm) and hypotension (MAP 58 mmHg). This anticipated crisis was managed with atropine and a supplemental ketamine bolus (0.3 mg/kg), successfully restoring hemodynamic stability. The procedure was completed uneventfully. In conclusion, this case demonstrates that a tailored anesthetic regimen, focused on intrinsic hemodynamic support and proactive crisis management, can be a safe and effective strategy in this high-risk cohort. The successful outcome hinged not on a single agent but on a comprehensive perioperative process encompassing meticulous optimization, a deliberate choice of anesthetic modality based on patient pathophysiology, goal-directed intraoperative therapy, and a structured transition to postoperative care.